Refinancing under yardstick regulation with investment cycles: The case of long-lived electricity network assets - Dominik Schober; Christoph Weber (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
In the context of yardstick regulation with long-lived assets, the influence of heterogeneous investment cycles on the ability to recover capital is found to be important. The application of efficient firm standards based on historic (straight-line) depreciation given heterogeneous investment and cost cycles will cause instantaneous yardstick levels below the long-run refinancing level. The efficient firm standard will prevent capital recovery in later periods. An illustrating example from electricity distribution illustrates the relevance of the problem. Finally, two alternatives, branch average cost yardstick determination and correction factors based on the share of capital under depreciation, are discussed.
Keywords: L51; L52; 330; yardstick regulation; infrastructure investment; capital-recovery; sustainable refinancing; electricity distribution